Cardiac troponins and autoimmunity: their role in the pathogenesis of myocarditis and of heart failure - Kaya, Ziya; Katus, Hugo; Rose, Noel R. (Clinical immunology, 2010)
Despite the widespread use of cardiac troponins as biomarkers for the diagnosis and quantitation of cardiac injury, the effect of troponin release and a possible autoimmune response to the troponins is unknown. Other investigators reported that programmed cell death-1 (PD-1)-receptor deficient mice developed severe cardiomyopathy with autoantibodies to troponin I. We found that immunization of genetically susceptible mice with troponin I but not troponin T induced a robust autoimmune response leading to marked inflammation and fibrosis in the myocardium. At later times, antibodies to cardiac myosin were detected in troponin-immunized mice. The severity of inflammation correlated with expression of chemokines RANTES, MIP-2, IP-10 and MCP-1 in the myocardium. Prior immunization with troponin I increased the severity of experimental infarctions, indicating that an autoimmune response to troponin I aggravates acute cardiac damage. Cardiac inflammation, fibrosis and functional impairment were transferred from immunized to naive recipients by CD4+ T cells, and the cytokine profile suggested both Th2 and Th17 profiles in A/J mice. Finally we identified an 18-mer of troponin I containing an immuno-dominant epitope.
Online veröffentlicht am 14. Mai 2009
Gesehen am 08.03.2023